Antimicrobial effect of zinc oxide nanoparticles on Campylobacter jejuni and Salmonella enterica serovar Enteritidis. Issue 4 (3rd April 2022) - He, Yiping; Capobianco, Joseph; Irwin, Peter; Reed, Sue; Lee, Joe
Abstract: Engineered nanoparticles have been explored for their potential to serve as additives to foods, their packages, and contact surfaces because they are stable in a wide range of harsh environments and display inherent antimicrobial properties. However, while nanometer sized particles have demonstrated unique properties that can potentially benefit food technologies, size and shape of the particles may have significant impact on their antimicrobial activities and toxicity as well. This manuscript characterized the size and morphology of five commercially available ZnO nanoparticles and determined the antimicrobial performance for two common foodborne pathogens, Campylobacter and Salmonella . The results indicate that all grades of ZnO powders displayed antimicrobial properties on Campylobacter within 30 min, and that statistical methods could not differentiate between the grades when treated as categorical variables. Similarly, ZnO powders were found to be effective antimicrobial agents for Salmonella, though longer exposure times were needed and the grades did not perform equally. From comparison of the particle size distribution data and microscopic images of the grades of ZnO powders used in the study, it can be deduced that not only size, but also morphology have an impact on the antimicrobial activity. Abstract : S . Enteritidis displayed an antimicrobial response that was inversely related to the size of the ZnO nanoparticle. The antimicrobial response of C. jejuni was independent of the ZnO particle size. C. jejuni is more sensitive to ZnO; the minimum inhibitory concentration was an order of magnitude lower than S . Enteritidis in the presence of the smallest and most effective nanoparticle. The primary cause of ZnO on C. jejuni cell death is likely due to oxidative stress induced by the reactive oxygen species from ZnO, not the direct contact between the particles and cells.